Yttrium-90 radioembolization for neuroendocrine liver metastases: baseline vascularity predicts cytoreduction efficacy - Anne Frisch; Johannes Kahn; Federico Collettini; Peter Steinhagen; Uli Fehrenbach; Bernhard Gebauer; Holger Amthauer; Imke Schatka; Paul Herzler; Gero Wieners; Willie M. Lüdemann (PLoS ONE, 2026)
Purpose This retrospective study in patients with neuroendocrine liver metastases analyzes baseline vascularity on MR as a predictor of tumour debulking after conventional Yttrium-90 transarterial radioembolization (TARE). Methods 30 patients who underwent TARE at our center between 2015 and 2022 were retrospectively assessed. Pre- and post-treatment target lesion volumes were measured as total tumor volume (TTV) and enhancing tumor volume (ETV). Cox-regression analyses as well as Kaplan-Meier statistics were used to evaluate baseline volumetric imaging parameters and clinical variables as predictors of survival. Results Mean patients’ age was 63 (SD 11) years, 15 were female (50%). The primary tumor was in the upper gastrointestinal tract in 13/30 cases (43%). Median overall survival (mOS) was 33.0 months (95%CI [21.2; 44.7]). Eligibility for peptide receptor radionuclide therapy (PRRT) was the single strongest predictor of survival with a hazard ratio of 0.22 (p = 0.024) and a mOS of 60.8 months whereas receptor-negative patients had the shortest survival of 7.0 months (p = 0.019). A baseline ETV/TTV ratio greater 50% was associated with a decrease in median ETV by 41% after lobar TARE compared to an increase by 18% in patients with poor baseline vascularity (p = 0.018). In the 17/30 patient who received systemic therapies exclusively before TARE, mOS was 15 vs. 6.8 months (p = 0.082). Prior PRRT did not significantly impact the change of ETV after TARE. Conclusion In lobar TARE for neuroendocrine liver metastases, high baseline vascularity shows an exploratory association with a significant reduction in viable tumor volume, warranting further investigation to improve patient selection.